Synthesis of nitrogen and sulfur co-doped reduced graphene oxide as efficient metal-free cocatalyst for the photo-activity enhancement of CdS - Han, W.; Chen, L.; Song, W.; Wang, Shaobin; Fan, X.; Li, Y.; Zhang, F.; Zhang, G.; Peng, W. (Elsevier BV, 2018)
© 2018 Elsevier B.V. Nitrogen and sulfur co-doped reduced graphene oxide (NS-rGO) was synthesized using a facile low temperature calcination method, which was then used as support and cocatalyst for the anchor of CdS. The obtained CdS/NS-rGO nanocomposites exhibit ultra-high photocatalytic activity for hydrogen evolution and 4-nitrophenol (4-NP) reduction under visible light (? = 420 nm). Their activity could also be adjusted by changing the doping amount of S and N, or by changing the ratios between CdS and NS-rGO. The optimum percentage of NS-rGO is 5 wt%, at which CdS/NS-rGO photocatalyst could achieve the highest H2evolution rate of 1701 µmol h–1g–1. Moreover, the reduction from 4-NP to 4-aminophenol (4-AP) could be completed within only 6 min over this optimized composite. NS-rGO here could provide more active sites as well as tune the band gap structure to increase the photo-activity. The density functional theory (DFT) calculations reveal that NS-rGO has a small Gibbs free energy for H* adsorption (?GH), which could increase the utilization efficency of photo-generated electrons for H2generation. NS-rGO is therefore an idea alternate cocatalyst of noble metals for new photocatalysts development.